PESANTREN DAN BONUS DEMOGRAFI DALAM MEWUJUDKAN SANTRI UNGGUL 2045 (Studi Wacana Visi Indonesia Emas) - Rosyid, Abdul (IAIN Madura, 2022)
In 2016, President Joko Widodo through the Ministry of National Development Planning gave the task of compiling a golden Indonesia Vision in 2045. The contains of vision are blue print and an ideal pictures that the Indonesia needs to achieve in 2045. Pesantren as one of the education providers need to respond to the discourse as a contribution between Pesantren and the government to succes the vision. Pesantren as human resources printers need to know the challenges and strategies, especially in that year 51% of Indonesia's population was of productive age or demographic bonus. This paper writes about the role and challenges of pesantren in facing the demographic bonus in the future. The data is written in analytical descriptive. The gap between educational institutions in Indonesia, especially Pesantren is getting fresh from the ratification of Presidential Decree No. 02 of 2021 concerning Pesantren funding.